The role of angiotensin I - converting enzyme (ACE) insertion/deletion gene polymorphism in hypertension and ACE inhibitor therapy: a narrative review - Handani, Dewa Ayu Sri; Zullies Ikawati; Hermawan, Adam (Indonesian Journal of Pharmacology and Therapy, 2023)
Primary hypertension is the most prevalent type of hypertension, which is primarily attributed to genetic factors. The angiotensin-converting enzyme (ACE) gene has emerged as a prominent candidate among the genetic factors influencing blood pressure regulation. The ACE gene encodes the ACE, which plays a crucial role in the renin-angiotensin system. The ACE gene insertion/deletion (I/D) polymorphism is a variation of the ACE gene that affects blood pressure regulation. Individuals with II, ID, and DD genotypes may exhibit distinct ACE plasma concentrations, potentially contributing to variations in blood pressure levels and response to ACE inhibitor therapy. This article aimed to provide a comprehensive overview of the relationship between the ACE I/D gene with hypertension and angiotensin-converting enzym inhibitor (ACEI) effectiveness. This article presents a narrative review encompassing relevant studies published between 2013 and 2023. A systematic search was conducted using reputable databases such as PubMed, Science Direct, and Scopus. Inclusion criteria were applied, resulting in the selection of 25 articles that met the predefined criteria. The analysis included 25 studies, comprising 5 articles that investigated the impact of ACEI therapy and 20 articles that examined the ACE I/D gene polymorphism in hypertensive populations without ACEI therapy. It can be concluded that compared to the I allele, the D allele of the ACE I/D gene is associated with a higher level of essential hypertension and a reduced ACEI response.